Trastornos de la conducta alimentaria, experiencias adversas vitales e imagen corporal: Una revisión sistemática: Eating disorders, life stressful events and body image: A systematic review - Idini, Ester; Barceló Soler, Alberto; Navarro Gil, Maria Teresa; Paredes Carreño, Pamela; Pérez Tausia, Daniel; Garcia Campayo, Javier (Revista de Psicopatología y Psicología Clínica, 2021)
Eating disorders, life stressful events and body image: A systematic review Abstract: Our objective was to clarify the relationship between adverse life events and the altered body image in eating disorders. We reviewed English and Spanish papers indexed in MEDLINE, PsycINFO and ScienceDirect from the last 10 years. We included 16 studies of which 37.5% focus on eating disorders. Sexual abuse, physical abuse, domestic violence, bullying and having experienced multiples adverse life events have been associated with overweight patients and high body dissatisfaction. Emotional abuse has been associated with underweight and body shape concerns. Posttraumatic symptoms and emotion dysregulation have been identified as mediating factors. Eating disorder psychopathology could be the response to a bad regulation of negative emotion coming from different adverse life events and this mechanism could underlie patiens’ body dissatisfaction. Keywords: eating disorders; adverse life events; bulimia nervosa; anorexia nervosa; binge-eating disorder; body image; body dissatisfaction; traumatic events. Resumen: El objetivo de este trabajo es esclarecer la relación entre experiencias adversas vitales y la alteración de la imagen corporal en los trastornos alimentarios. Se han revisado trabajos en inglés y castellano indexados en MEDLINE, PsychoINFO y ScienceDirect en los últimos 10 años. Se han incluido 16 estudios de los cuales, el 37.5% se centra en trastornos de la alimentación. El abuso sexual, el físico, la violencia intrafamiliar, el acoso escolar y la suma de diferentes experiencias adversas vitales identifican pacientes con sobrepeso y alta insatisfacción corporal. El abuso emocional se ha asociado a bajo peso y preocupación entorno a la figura. La relación con la imagen corporal está mediada por clínica postraumática y la desregulación emocional. La clínica alimentaria es una respuesta a un mal manejo de emociones negativas derivadas de diferentes experiencias adversas y este mecanismo podría estar en la base de la insatisfacción corporal de los pacientes. Palabras clave: trastornos de la alimentación; experiencias adversas vitales; bulimia nerviosa; anorexia nerviosa; trastorno de atracón; imagen corporal; insatisfacción corporal; eventos traumáticos.